A Pragmatic Analysis of Intensifiers in Boris Jonson’s Political Interview - Zidan, Ahmed Jiad; Ahmed, Muslih Shwaysh (Al-Adab Journal, 2022)
The present study is concerned with English intensifiers as a linguistic means of intensification. They are a complex phenomenon. This complexity is related to the definition and classification of intensifiers. The current study has been conducted to find a very comprehensive classification of intensifiers to analyze them pragmatically in a systematic framework and get a general picture of the pragmatic functions of the intensifiers in this interview. These pragmatic functions are determined by the modification of both illocutionary force and speech acts, besides showing the effect of intensifiers on the other pragmatic functions. The purpose behind the combination of all the above models is to analyze intensifiers pragmatically in a systematic way in the present study. The aims of the study are the following;(i) investigating the frequent use of intensifiers in this political interview, (ii) investigating the pragmatic function of intensifiers, and (iii) examining how the politicians function/use the intensifiers in this political interview. According to these aims, it is hypothesized that;(i) politicians in their interviews frequently use intensifiers, (ii) investigating that English intensifiers have pragmatic functions, and (iii) they use intensifiers in their political interviews for a specific intended meaning as a way, for instance, to express the degree of their feelings, beliefs, and attitudes of persuasion, agreement or any other pragmatic functions. To achieve the aims and the hypotheses of this study, the researcher has selected Boris Johnson’s political interview to analyse pragmatically the intensifiers used by him. The intensifiers are identified depending on the classification of Quirk et al.’s (1985). Two models are adopted for the analysis of the pragmatic functions of these intensifiers to conduct a systematic pragmatic analysis. They are: (a) Bazzanella et al. (1991), Cacchiani (2009) & Holmes (1984) for the analysis of modification for; (i)illocutionary force(ii) speech acts, and (b) Urbanova (2003) for Boosting and Attenuating other pragmatic functions. According to data analysis and discussions, the study finds that interlocutors have used different types of intensifiers for various purposes. It has found that intensifiers that express the modal meaning, and those used in the content/discourse oriented are higher in frequency than other tendencies. Moreover, it has also found that the intensifiers of both types, amplifiers and downtoners, have been used to modify the dimensions of the illocutionary force of speech acts. According to the aims and the analysis models, the study is qualitatively designed based on the qualitative content analysis procedure. It was only quantitative to identify the individual and the total use of intensifiers in the interview. According to the discussion and the findings of the data analysis, the study has arrived at the following conclusions:1-The intensifiers are not only used to show the mechanism of modification, but they are also used to show the interpersonal functions such as conveying the speaker’s commitment or attitude toward the propositional content or the addressee. 2- The interlocutors use most of the intensifiers to convey the modal meaning. The modal meaning is only used to boost or attenuate the speech acts by both the speaker or the addressee. 3- Using a small number of intensifiers to convey the affective meaning by the politician is due to the fact that they cannot speak about their own private life. Their speech is actually authorized by their party and their coalition.